Age assessment of unaccompanied foreign minors: an analyses of knowledge and practices among Italian pediatricians - Danilo Buonsenso; Manuela Ceccarelli; Bettina Camara; Donatella Angelone; Valentina Burzio; Simona La Placa; Piero Valentini; on behalf of GLNBM-SIP* an (BMC, 2024)
Abstract Background Increases in migration patterns in the recent years have led to a continuously growing number of unaccompanied foreign minors (UFMs) entering Italy. As part of processing and integration, age assessment is performed by pediatricians upon request of regulatory bodies. Updated guidelines for age estimation procedures were published in 2020 in order to prioritize the well-being of the minors and the accuracy of the assessment. Nonetheless, literature suggests that the recently established multidisciplinary approach has not yet been widely adopted by physicians. Methods A cross-sectional exploratory survey was distributed to pediatricians in Italy in order to gauge their range of experience with UFMs and age assessment protocols. Results In total 344 pediatricians participated in the survey, originating from varied regions in Italy. Out of pediatricians who reported conducting age assessment procedures (38.9%), only a small fraction (14.2%) confirmed being knowledgeable about the methodology. Instead, a significant portion (28.8% and 56.4%) either had partial awareness or lacked knowledge of these procedures. These responses significantly differed when comparing hospital and outpatient pediatricians or according to their geographical area of work (p <0.05). Conclusion Survey responses suggest that a gap in awareness and experience regarding a multidisciplinary approach to age estimations still exists, likely in part due to a lack of resources, especially at the regional level. In the future, efforts towards the education of professionals and mobilization of resources for investment in the field will be crucial for the improvement of work with UFMs and other migrant populations.